Inventarisasi dan Identifikasi Jenis Tumbuhan Famili Poaceae di Sekitar Cibiru, Bandung, Jawa Barat - Maulina Azizah; Melza Aulia; Ateng Supriyatna (Universitas Katolik Widya Karya Malang, 2023)
Poaceae is a cosmopolitan group of grasses whose diversity is very high in Indonesia due to the diversity of ecosystems and geographical conditions that support the growth of the group. The grasses are easy to grow and resistant to drought and waterlogging. Poaceae are used as food ingredients in Indonesia and natural greening materials that play a role in natural balance. This study aims to inventory and identify plant species of the Poaceae family around Cibiru, Bandung, West Java. The method used in this research is descriptive qualitative method. The research was conducted by exploration, namely exploring along the research location and collecting information on the existence of plant species of the Poaceae family. Plant identification was carried out by matching plant morphological characters using various literature both identification books, journals, and websites. There were five species found including Oryza sativa, Zea mays, Imperata cylindrica, Panicum repens, and Panicum maximum.